Post-acquisition TikTok and Tokopedia: Optimization marketing media to encourage entrepreneurship on Sumatra Island - Wulandari, Poppy; Mawaddah; Purba, Ade Rasinta Herli Kristiani (Priviet Social Sciences Journal, 2025)
This research investigates the potential of TikTok as a digital marketing platform for fostering entrepreneurship on Sumatra Island, Indonesia. The study addresses the gap in the current literature regarding the suboptimal use of digital marketing tools in the region, particularly TikTok, which remains under-utilized despite its potential to enhance entrepreneurial growth. Using a qualitative research approach, data was collected through in-depth interviews with six informants, three TikTok sellers and three affiliates from Aceh, North Sumatra, and West Sumatra. Findings indicate that TikTok serves as an effective and cost-efficient platform for entrepreneurs, offering a dual function as both an entertainment and shopping medium. However, the study reveals challenges, such as limited digital financial literacy and an underdeveloped application of marketing strategies on the island. The research contributes to understanding the dynamics of digital marketing adoption in Sumatra, highlighting the necessity of enhancing digital financial literacy and maximizing the use of the platform, for example, TikTok to boost entrepreneurial independence. The implications of this study suggest the importance of integrating digital tools in regional economic policies to foster inclusive growth. The study also acknowledges limitations such as the small sample size and the focused geographical scope which recommend future research with broader, more diverse samples and a mixed-methods approach to explore long-term business sustainability and the comparative effectiveness of various digital platforms.